The Perceptions of Thai and International Lecturers of English in Using an Online Platform - Sonkaew, Thitichaya; Pattanapongpitak, Harinfa (Journal of Community Development Research (Humanities and Social Sciences); Vol 17 No 3 (2024): July - September 2024, 2024)
Even with the resumption of physical classes following the pandemic outbreak, various educational institutions tend to remain using online platforms, although not entirely employed. Considering this matter, it is plausible to scrutinize perceptions of instructors as inevitable users, as well as the effectiveness, advantages, and disadvantages of online instructional platforms. The objective of this study is to investigate the viewpoints of lecturers who remain utilizing virtual platforms. It examines the perceptions of Thai and international university English lecturers regarding the utilization of online platforms and explores any difficulties they might have encountered in their EFL classes. Adopting a qualitative approach, the data were collected through semi-structured interviews. The findings indicate that Thai and international English instructors at a Thai university view online platforms positively due to their user-friendliness and practicality. Key factors influencing these perceptions include perceived usefulness, ease of use, and self-efficacy. The benefits highlighted in the research encompass class accessibility, time and cost savings, and enhanced class organization. However, despite recognizing these advantages, there is a preference for traditional onsite classes over online alternatives. This may result from challenges experienced in online classes, notably related to students, such as Internet connectivity issues, a less motivating atmosphere, concerns over academic integrity, and diminished teacher-student interaction. Consequently, while online platforms can serve as supplementary resources for English classes, they may not fully replace traditional onsite classes but could be utilized as substitutes when required. Keywords: Online Platform, Online Learning and Teaching, English Teaching, Teachers’ Perception, Problems in Online Classes, Tat